Checklists of Species of Ergasilus von Nordmann, 1832 (Copepoda: Ergasilidae) Parasitic on Fishes of Iraq - Mhaisen, Furhan T.; Al-Daraji, Salem A. M. (Iraqi Journal of Aquaculture, 2023)
Surveying of 144 literature concerning occurrence of the copepod parasites of the genus Ergasilus parasitizing fishes of Iraq, indicated that there are 11 identified species of Ergasilus von Nordmann, 1832 as well as some unidentified species of this genus infecting 38 fish species. The infections were distributed in fishes from Tigris, Euphrates and Shatt Al-Arab rivers and some of their tributaries, as well as in some lakes, marshes, drainage networks, many fish ponds and floating cages in different parts of Iraq, in addition to marine waters of the Arab Gulf. Among the infected fishes, the mugilid fish Planiliza subviridis was infected with the highest number of Ergasilus species (eight species), followed by Carasobarbus luteus, Cyprinus carpio, Leuciscus vorax and Planiliza abu (seven parasite species each), while seven fish species were infected with only one Ergasilus species each. Among Ergasilus species, E. sieboldi was infecting a total of 25 different fish species, while each of E. iraquensis, E. lizae and E. synanceiensis were detected from one fish host species.